An open clinical trial of reboxetine in the treatment of social phobia - Atmaca, M; Tezcan, E; Kuloglu, M (Lippincott Williams & Wilkins, 2003)
[Abstract Not Available]
Keywords: Double-Blind; Moclobemide; Phenelzine